Altered CD45 expression and disease. - Tchilian, E; Beverley, P (2006)
CD45, the leucocyte common antigen, is a haemopoietic cell-specific tyrosine phosphatase. Many isoforms are generated by alternative splicing, but their function remains obscure. The extracellular domain of CD45 is highly polymorphic in all vertebrates. Importantly, human polymorphic variants that alter CD45 isoform expression are associated with autoimmune and infectious diseases, establishing CD45 as an important immunomodulator with a significant influence on disease burden. Here, we discuss the new opportunities provided by the human variants for investigating and understanding how CD45 regulates antigen receptor signalling, cytokine responses and apoptosis.